KAPABILITAS WIDYAISWARA DALAM PENINGKATAN MUTU PEMBELAJARAN PADA LEMBAGA PENDIDIKAN DAN PELATIHAN KEAGAMAAN BANJARMASIN - Zarkani Zarkani (Balai Diklat Keagamaan Banjarmasin, 2022)
Widyaiswara has a very important role in carrying out learning with students. The role of widyaiswara cannot be replaced by any media, so its existence as the core of learning must remain. Quality of learning is the ability possessed by educational and training institutions in implementing learning effectively and efficiently, so as to produce high-value benefits for the achievement of predetermined learning objectives. Quality improvement components that take part in its implementation are the appearance of resource persons, mastery of material/curriculum, use of teaching methods, utilization of educational tools/facilities, implementation of learning and evaluation. The problem of widyaiswara in improving the quality of learning is related to the existence of widyaiswara who have less educational qualifications, the professionalism of the resource persons in carrying out their duties is still low, the preparation of the widyaiswara to carry out teaching is not stable, the lack of use of media and learning resources and the low level of innovativeness and creativity teach widyaiswara. To achieve the quality of learning, firstly, the widyaiswara must equip himself with a number of competencies in the field of teaching, both carried out by himself and the development carried out by the coaching agency. The debriefing activities are carried out continuously in line with the development and demands of the educational world, so that in the end it will form a more professional attitude from the widyaiswara themselves.